الحدود بين التعبد والتعليل = al-Hudud baina al-taábbud wa-al-ta'lil - Laeba, Muhammad; Eswikar, Abdul Majid Qasim Abdul al-Majid (International Islamic University Press, 2014)

(untitled)
This article discusses the question of analogical reasoning (qiyÉs) in the prescribed categorical penalties (ÍudËd) in order show whether they are predominantly subject to ratiocination and causation (taÑlÊl) or to mere devotional submission (tÑabbud). The study has demonstrated that, as a matter of general principle, ÍudËd penalties are of a devotional character, they are individually subject to ratiocination, and hence they constitutes a base of analogical reasoning for arising new criminal issues. It has also shown that the majority of the jurists subscribe to ratiocination and causation in ÍudËd provided its requirements are fulfilled. Those who reject such a proposition, which is the position of most Hanafi jurists, do so not on the ground of devotional submission, but on the ground that analogical reasoning holds only for evaluative judgements (aÍkÉm) and not for names (asmÉ’). For them, linguistic matters are not established through analogies by through authority and transmission. The article has arrived at the conclusion that there is a wide room for analogical reasoning in ÍudËd whereby new criminal problems can be dealt with, no matter how variegated and complicated they might be.